2022
DOI: 10.3389/fpubh.2022.791550
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparity in the Incidence of Scoliosis Among Adolescents in Tianzhu Tibetan Autonomous County, China

Abstract: ObjectivesTo determine the influence of ethnic disparities, socioeconomic status (SES) and hukou on the incidence of scoliosis.MethodsWe enrolled 2,445 junior high school students (Han: 1,153; ethnic minorities: 1,292) aged 12–16 years from two schools in Tianzhu Tibetan Autonomous County, Gansu Province from November 2020 to February 2021. We measured the angle of trunk rotation (ATR) using a scoliometer. Two-factor analysis of variance was used to comparatively analyze differences in the ATR according to eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Nevertheless, there was no statistically significant difference in the proportion of individuals with a Cobb angle ≥40° between the two sex. The prevalence of IS in Yunnan Province was found to be lower than that in certain regions, such as the Qinghai-Tibet Plateau, which is characterized by a high-altitude environment and a predominantly Tibetan population; However, the prevalence of IS in Yunnan Province showed a similar trend to previous studies in other ethnic groups and regions in China ( 6 , 34 , 35 ). Furthermore, it was observed that the incidence of IS exhibited a gradual rise in correlation with advancing age, peaking in the 13–14 years age range, followed by a subsequent gradual decline.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Nevertheless, there was no statistically significant difference in the proportion of individuals with a Cobb angle ≥40° between the two sex. The prevalence of IS in Yunnan Province was found to be lower than that in certain regions, such as the Qinghai-Tibet Plateau, which is characterized by a high-altitude environment and a predominantly Tibetan population; However, the prevalence of IS in Yunnan Province showed a similar trend to previous studies in other ethnic groups and regions in China ( 6 , 34 , 35 ). Furthermore, it was observed that the incidence of IS exhibited a gradual rise in correlation with advancing age, peaking in the 13–14 years age range, followed by a subsequent gradual decline.…”
Section: Discussionsupporting
confidence: 52%
“…However, it falls within the range of prevalence rates observed in different provinces in China (ranging from 0.11% to 2.64%) ( 9 , 10 , 34 , 35 ). Research indicates that the prevalence of AIS is associated with various factors, such as ethnicity, altitude of residence, and socioeconomic status ( 6 , 35 ). The prevalence of AIS varies among countries, including the United States (0.52%) ( 8 ), Japan (0.87%) ( 36 ), Saudi Arabia (0.78%) ( 37 ), India (0.61%) ( 33 ), Korea (0.497%) ( 38 ), and Iran (0.62%) ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations